A settler physician perspective on Indigenous health, truth, and reconciliation (Canadian Medical Education Journal, 2018)
This brief report presents one settler physician’s perspectives on our responsibility to engage in reconciliation and decolonize our healthcare institutions. It draws from existing literature to identify key actions for reconciliation in health care. These include i) engaging Indigenous peoples as leaders and equal partners in developing health interventions, ii) increasing our awareness and education around the colonial history and settler presence in Canada, including our role in the ongoing oppression of Indigenous peoples, iii) providing services in ways that recognize and mitigate colonial determinants of health, and iii) practicing cultural safety at an individual level and advocating for it at a structural level. These actions can be realized through educational interventions and ongoing reflexivity among medical trainees and practicing physicians.